Sobre subvariedades totalmente reais - Carneiro, José Loester Sá (2011)
Complex analytic submanifolds and totally real submanifolds are two typical classes among all submanifolds of an almost Hermitian manifolds. In this work, some characterizations of totally real submanifolds are given. Moreover some classifications of totally real submanifolds in complex space forms are obtained.